The type of approach (medial versus lateral) influences TKA component rotation in total knee arthroplasty - a clinical study using 3D-CT. Issue 4 (27th April 2017) - Schiapparelli, Filippo-Franco; Amsler, Felix; Hirschmann, Michael
Aims and Objectives: : The purpose of this study was to investigate if the type of approach (medial parapatellar approach (MPA) versus lateral parapatellar subvastus approach with tibial tubercle osteotomy (LPA)) influences the rotation of femoral and/or tibial component and leg axis in total knee arthroplasty (TKA). Materials and Methods: : This study included 200 consecutive patients in whom TKA was performed using either a parapatellar medial (n=162, MPA) or parapatellar lateral subvastus approach with tibial tubercle osteotomy (n=38, LPA). All patients underwent clinical follow-up, standardised radiographs and computed radiography (CT). TKA components' position and the whole leg axis were assessed on 3D reconstructed CT scans (sagittal, coronal and rotational). Mean values of TKA component position and the whole leg alignment of both groups were compared using a T-test. The tibial component was graded as internally rotated (< 3° of external rotation (ER)), neutral rotation (equal or between 3° and 6° of ER) and and externally rotated (>6° ER). The femoral component was graded as internally rotated (< 3° of internal rotation (IR)), neutral rotation (equal or between -3° IR and 3° of ER) and externally rotated (>3° ER). Results: : There was no significant difference in terms of whole leg axis after TKA between both groups (MPA: 0.2° valgus ± 3.4; LPA: 0.0° valgus ± 3.5). Means of tibial component position were 2.7° ER ± 6.1 (MPA) and 7.6° ER ± 5.4 (LPA). Patients of group LPA presented a significantly less internally rotated (LPA: 18.4%; MPA: 48.8%) and more externally rotated (LPA: 52.6%; MPA: 22.8%) tibial component (p<0.001). No significant differences were seen for the femoral component position, tibial valgus/varus and tibial slope. Conclusion: : The type of approach significantly influences the tibial TKA component rotation. It appears that a MPA tends to internally rotate the tibial TKA component and a LPA tends to externally rotate the tibial TKA.